A More COMPLETE Picture of Revascularization in STEMI - Køber, Lars; Engstrøm, Thomas (The New England journal of medicine, 2019)
Up to half of patients presenting with acute ST-segment elevation myocardial infarction (STEMI) have multivessel coronary artery disease, and American College of Cardiology–American Heart Association–European Society of Cardiology guidelines have a class IIb recommendation for the treatment of nonculprit lesions. 1-4 Four intermediate-sized trials have shown that complete revascularization is safe and reduces the risk of repeat revascularization. 5-8 Until now, a general strategy of complete revascularization has not been shown to reduce the risk of hard outcomes, such as death and recurrent myocardial infarction. In addition, it has been suggested that identification of nonculprit lesions relevant for complete revascularization should be . . . Lars Køber and Thomas Engstrøm comment on the findings of the COMPLETE trial and their implications for the use of complete revascularization in patients with STEMI and multivessel disease.